1991
DOI: 10.1139/z91-141
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the number of glochidia produced by clams (Anodonta grandis simpsoniana Lea), attaching to yellow perch (Perca flavescens), and surviving to various ages in Narrow Lake, Alberta

Abstract: Between May 1986 and March 1989, the density, breeding cycle, and glochidia production of the unionid clam Anodonta grandis simpsoniana, and the population size and intensity of glochidia infestation of yellow perch, Perca flavescens, were evaluated in Narrow Lake, Alberta. The total number of glochidia produced was compared with the number of glochidia infesting yellow perch, and clam recruitment to age 2 and adulthood was estimated. Clams carried eggs and glochidia between July and, dependent on the prevaili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In Margaritifera margaritifera, an average of 64% of females reproduces in a given year with the remainder of females in a resting stage (Bauer, 1987). For North American unionids, a number of studies reported high female participation in reproduction (>85% of females reproducing in a given year) (Yokely, 1972;Trdan, 1981;Jansen & Hanson, 1991;Bruenderman & Neves, 1993;Woody & Holland-Bartels, 1993;Haggerty & Garner, 2000), whereas in others, the percentage of gravid females during the peak brooding period ranged from 64 to 75% (Yeager & Neves, 1986;Haggerty et al, 1995;Garner et al, 1999). It is unclear whether the low numbers found in these latter studies are indicative of lower female participation in reproduction, or simply a result of a protracted brooding period with low brooding synchrony among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In Margaritifera margaritifera, an average of 64% of females reproduces in a given year with the remainder of females in a resting stage (Bauer, 1987). For North American unionids, a number of studies reported high female participation in reproduction (>85% of females reproducing in a given year) (Yokely, 1972;Trdan, 1981;Jansen & Hanson, 1991;Bruenderman & Neves, 1993;Woody & Holland-Bartels, 1993;Haggerty & Garner, 2000), whereas in others, the percentage of gravid females during the peak brooding period ranged from 64 to 75% (Yeager & Neves, 1986;Haggerty et al, 1995;Garner et al, 1999). It is unclear whether the low numbers found in these latter studies are indicative of lower female participation in reproduction, or simply a result of a protracted brooding period with low brooding synchrony among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A well-studied population in Narrow Lake (near source of mussels for this study) of this species was assumed to be hermaphroditic by Jansen and Hanson (1991) based on the proportions of gravid specimens in various months and years in the population. A larger sample size of non-gravid mussels would have been preferred in the present study to confirm whether the changes observed in the levels of Vtg-like protein reflect exposure to CECs with estrogenic activity in wastewater.…”
Section: Biomarkersmentioning
confidence: 99%
“…Coker et al, 1922;Sebastyen, 1942;Crowley, 1957;Negus, 1966;Heard, 1975;Coon, Ekblad & Trygstad, 1977;Haukioja & Hakala, 1978;McCuaig & Green, 1983;Mitchell, 1984;Hinch, Bailey & Green, 1986;Bauer, 1987;Hanson, Mackay & Prepas, 1988;Jansen & Hanson, 1990;Heller, 1990;Huebner, Malley & Donkersloot, 1990). The assumption that external annuli are laid down yearly is only rarely checked, and recent tests yield equivocal results.…”
Section: Introductionmentioning
confidence: 99%